Bernstein`s construction of movement model and contemporary motor control and motor learning theories - Petrynski, W. (Human Movement, 2007)
The paper presents Bernstein`s five-level model of motor control and motor learning in humans: A - muscle tonus, B - muscle synergies, C - spatial mobility, D - complex motor performances, and E - symbolic representations of motor performances. Each level corresponds to a group of sensorimotor actions, i.e. a way of using receptors, effectors, and particular components of the central nervous system. The higher the levels, the more complex sensorimotor task it can control. Each level corresponds to its own theoretical control model: levels B and C - to Gibson`s ecological theory and the Equilibrium Point Hypothesis (EPH) by Feldman; level D - to the "cybernetic" models, e.g. Schmidt`s scheme. For storing and transferring information, levels A, B and C use mainly the sensory code, while levels D and E the symbolic code. The motor command delivered to a muscle has to always be expressed in the sensory code; hence in the control system it is necessary to "translate" the sensory code into symbolic one and vice versa. Consequently, it is possible to create two motor learning models: model "0", describing the circulation of sole sensory information between levels A, B and C, and model "8" assuming two circles of information exchange: lower, sensory, at levels A, B and C; and higher, symbolic, at levels D and E. In the ABC region we deal with data driven processes, for which behaviourism can serve as a theoretical basis, while the DE region features conceptually driven processes which require some cognitive explanation. Besides, in the process of motor learning an important part is played by information "chunking", necessary for transcoding. The cooperation of sensory, short-term, long-term and working memories is also of vital importance.